Association of anti-HBc seropositivity with undetectable or low level anti-HBs (<100) in anti-HCV positive blood donor population. - Barradas, A (2012)
In this data we observed the association between confirmed. Anti-HCV positive and Anti-HBc positive with low level (<100) or undetectable Anti-HBs. b) ./. c) Between May 1995 to December 2001 we collected and analysed 24989 samples from volunteer blood donors. In this samples we performed the following tests Anti?HCV (Ortho), confirmed for PCR (Roche) or RIBA (Innogenetics), Anti-HBc (Dade-Behreing/Abbott, Anti-HBs (Abbott) and HCV genotype (Innogenetics). d) We found between Anti-HCV neg. population 6,94% positives Anti-HBc and 25,65% of them was Anti-HBs low level or undetectable. In the population we found 0,148% of confirmed Anti-HCV reactive donors, among them we found 51,35% of Anti-HBc positivity and between the last ones 78,9% had low level or undetectavel Anti-HBs. The ALT average level in the Anti-HCV positive donors was: Anti-HBc negative donors: 140,28 Ani-HBc positives with high level of Anti-HBs: 50,48 Anti-HBc positives with low or undetectable level of Anti-HBs: 64,11 e) The Anti-HCV confirmed donors associated to the Anti-HBc positives with low level or undetectable Anti-HBs (78,9%). Comparing with the Anti-HCV negative donors, positive for Anti?HBc and with low level or undetectable Anti-HBs (25,65%). This is statistically relevant.